Study of the outbreaks of bovine rabies occurrence in Orellana, Ecuador the 2012-2018 period - Guamán-Rivera, Santiago Alexander; Castro-Guamán, Walter Efraín; González-Marcillo, Raúl Lorenzo; Guerrero-Pincay, Ángela Edith (Revista Arbitrada Interdisciplinaria Koinonía, 2020)
In Ecuador, a government institution is responsible for applying regulations for official animal control of rabies and reducing to non-dangerous levels. However, in Orellana, no documented bibliography serves as a resource to assess risk. An observational study was carried out of the bovine rabies outbreaks occurrences from 2012 to 2018 period. With the SAS statistical package were obtained; descriptive statistics as well as interquartile values of the cases presented for then build an endemic channel and shows accumulated prevalence rate for each year. We resulted indicated that was presented a total of 44 cases to rabies during all period study. Finally, we can tell the frequency of the disease did not show marked seasonality due to climatic factors.